PENGELOLAAN DANA DONASI VIHARA PADA VIHARA BUDHI DHARMA - Wijaya, Henryanto; Clessia Caroline Reonaldi; Jessica (Jurnal Serina Abdimas, 2025)
Vihara Budhi Dharma is a place of worship for Buddhists. A lack of understanding regarding fund management in religious foundations can lead to disorder in fund management, which has the potential to result in losses. Therefore, to broaden the knowledge of the administrators, our PKM team from the Faculty of Economics and Business, Tarumanagara University will conduct socialization and training on fund management for religious foundations. Through this activity, it is hoped that the religious foundation can implement transparent, accountable fund management that complies with applicable accounting standards. Attention to financial record-keeping and the preparation of financial reports is crucial as it reflects the financial condition of the religious foundation. This is important for increasing donor trust and for carrying out both religious and social activities. The advancement of technology also serves as a tool for effective fund management. Skilled, competent, and quality Human Resources (HR) are also essential for the successful implementation of this initiative. The solution we provide is to conduct a Focus Group Discussion (FGD) together with the temple management to identify the problems in Vihara Budhi Dharma. Our team has found that socialization and training on how to manage temple donation funds are necessary. This socialization and training will also include accounting and finance training, financial planning stages, strategy implementation, human resources development, and technology utilization. It is hoped that through this series of processes, Vihara Budhi Dharma will be able to produce positive outcomes, manage its funds effectively, enhance donor trust, and ensure the financial sustainability of the temple in carrying out its religious and social programs. ABSTRAK Vihara Budhi Dharma merupakan tempat beribadah keagamaan bagi umat Buddha. Kurangnya pemahaman mengenai pengelolaan dana pada Yayasan keagamaan dapat menimbulkan ketidakteraturan dalam pengelolaan dana yang berpotensi mengakibatkan kerugian. Sehingga dalam rangka memperluas wawasan pengurus tersebut, tim PKM kami yang berasal dari Fakultas Ekonomi dan Bisnis Universitas Tarumanagara akan melaksanakan sosialisasi dan pelatihan mengenai pengelolaan dana bagi Yayasan keagamaan. Dengan berlangsungnya kegiatan ini, diharapkan agar Yayasan keagamaan dapat menerapkan pengelolaan dana yang transparan, akuntabel, dan sesuai standar akuntansi yang berlaku. Dimulai dari pencatatan keuangan hingga penyusunan laporan keuangan sangat penting untuk diperhatikan karena dapat mencerminkan kondisi keuangan Yayasan keagamaan. Hal ini tentunya menjadi hal yang penting untuk meningkatkan kepercayaan donatur dan juga dalam menjalankan kegiatan keagamaan maupun sosial. Berkembangnya teknologi juga menjadi salah satu sarana dalam melaksanakan pengelolaan dana. Sumber Daya Manusia (SDM) yang cakap, kompeten, dan berkualitas juga menunjang pelaksanaan ini. Solusi yang dapat kami berikan adalah dengan melakukan Forum Group Discussion (FGD) bersama dengan pengurus vihara untuk mengidentifikasi masalah-masalah yang dialami. Tim kami menemukan bahwa sosialisasi dan pelatihan mengenai cara pengelolaan dana donasi vihara perlu untuk dilaksanakan. Sosialisasi dan pelatihan ini juga dilengkapi dengan pelatihan akuntansi dan keuangan, tahapan perencanaan keuangan, penerapan strategi, pengembangan sumber daya manusia (SDM), serta pemanfaatan teknologi. Diharapkan melalui serangkaian proses tersebut, Vihara Budhi Dharma mampu menghasilkan output yang positif, mengelola dananya secara efektif, meningkatkan kepercayaan donator, sehingga dapat menjaga keberlanjutan keuangan vihara dalam menjalankan program-program keagamaan dan sosialnya.